2020
DOI: 10.3389/fphys.2020.598779
|View full text |Cite
|
Sign up to set email alerts
|

KV7 Channel Expression and Function Within Rat Mesenteric Endothelial Cells

Abstract: Background and Purpose: Arterial diameter is dictated by the contractile state of the vascular smooth muscle cells (VSMCs), which is modulated by direct and indirect inputs from endothelial cells (ECs). Modulators of KCNQ-encoded kV7 channels have considerable impact on arterial diameter and these channels are known to be expressed in VSMCs but not yet defined in ECs. However, expression of kV7 channels in ECs would add an extra level of vascular control. This study aims to characterize the expression and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…Our data show that a high-sodium environment also reduced phosphorylated SPAK compared with the baseline sodium control group (Figure 5C) [21]. Among the vasoactive factors, eNOS is a major endothelial-derived mechanism regulating lymphatic dynamics, which is regulated by activity of NKCC1 [23]. Exposing LECs to a high-sodium environment caused a sig-nificant reduction in eNOS activity as measured by the amount of phosphorylated eNOS protein (Figure 6A).…”
Section: High Sodium Environment Changed Contractility Of Renal Lymph...mentioning
confidence: 63%
See 3 more Smart Citations
“…Our data show that a high-sodium environment also reduced phosphorylated SPAK compared with the baseline sodium control group (Figure 5C) [21]. Among the vasoactive factors, eNOS is a major endothelial-derived mechanism regulating lymphatic dynamics, which is regulated by activity of NKCC1 [23]. Exposing LECs to a high-sodium environment caused a sig-nificant reduction in eNOS activity as measured by the amount of phosphorylated eNOS protein (Figure 6A).…”
Section: High Sodium Environment Changed Contractility Of Renal Lymph...mentioning
confidence: 63%
“…Although kidneys are central in Na+ homeostasis, little is understood about Na+ effects on renal lymphatics. The current studies provide new insights into regulation of renal lymphatic network by showing (1) proteinuric kidney injury increases renal Na+ by 23 Na/1H MRI and direct sampling of renal lymphatic fluid shows elevated Na+ concentration while plasma Na+ is unchanged (2) high Na+ and furosemide inhibition of NKCC1 decrease lymphatic vessel contraction amplitude and ejection fraction in isolated renal lymphatic vessels, (3) a high Na+ environment decreases phosphorated-NKCC1, phosphorylated SPAK, an upstream kinase, and phosphorylated eNOS, a downstream vasoactive factor, and (4) a high Na+ environment together with renal injury contribute to a blunted lymphatic response in PAN-injured kidneys.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Immunocytochemistry with an antibody for K V 7.1 validated by overexpression studies (Figure S1) showed a significant reduction in total cell fluorescence (A.U) in Kcnq1 morpholino‐transfected arteries when compared to mismatch control (Figure 5a–c). Functionally, arteries incubated with mismatch control produced a significantly greater relaxant response to 300 nmol·L −1 K V 7.1 activator ML277 (Baldwin et al, 2020; Yu et al, 2013) compared to Kcnq1 morpholino‐transfected arteries (Figure 5d). Similarly, relaxation produced by 1 μmol·L −1 MRE‐269 was greater in arteries transfected with mismatch control morpholino when compared Kcnq1 morpholino‐transfected arteries (Figure 5e).…”
Section: Resultsmentioning
confidence: 91%